Strategies for Cultivating Cultural Literacy and Creativity for Early Childhood through Calligraphy Learning: Strategies for Cultivating Cultural Literacy and Creativity for Early Childhood through Calligraphy Learning - Ulfa, Mutia; Harisman Saputra, Rocky (Universitas Islam Balitar, 2025)
This study explores strategies for cultivating cultural literacy and creativity in early childhood through calligraphy learning. Cultural literacy plays a crucial role in shaping children's understanding of artistic heritage, while calligraphy serves as an effective medium for enhancing fine motor skills, creativity, and appreciation of cultural values. Using a qualitative approach, this research examines calligraphy education at PAUD Ishlahul Muslimin Senteluk, Batulayar, West Lombok, through observations, interviews, and document analysis. The findings highlight that calligraphy learning fosters cultural awareness, social skills, and creative thinking among young children. Additionally, integrating calligraphy into early childhood education helps develop patience, discipline, and cognitive abilities. The study emphasizes the need for teacher training and adequate resources to optimize calligraphy-based cultural literacy programs. Future research should explore the long-term impact of calligraphy learning on children's socio-emotional development and its implementation in diverse educational settings.